Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Ask your questions and receive precise answers from experienced professionals across different disciplines. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\( x^4 - 5x^2 - 14 = 0 \)[/tex] by factoring, let's go through the process step by step.
1. Substitute [tex]\( y = x^2 \)[/tex]:
This substitution simplifies the equation. Let [tex]\( y = x^2 \)[/tex], then the equation becomes:
[tex]\[ y^2 - 5y - 14 = 0 \][/tex]
2. Solve the quadratic equation [tex]\( y^2 - 5y - 14 = 0 \)[/tex]:
This is a standard quadratic equation. To solve it, we can use the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -5 \)[/tex], and [tex]\( c = -14 \)[/tex]. Plugging these values into the quadratic formula gives:
[tex]\[ y = \frac{5 \pm \sqrt{25 + 56}}{2} \][/tex]
[tex]\[ y = \frac{5 \pm \sqrt{81}}{2} \][/tex]
[tex]\[ y = \frac{5 \pm 9}{2} \][/tex]
3. Calculate the solutions for [tex]\( y \)[/tex]:
There are two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{5 + 9}{2} = \frac{14}{2} = 7 \][/tex]
and
[tex]\[ y = \frac{5 - 9}{2} = \frac{-4}{2} = -2 \][/tex]
4. Back-substitute [tex]\( y = x^2 \)[/tex] to find [tex]\( x \)[/tex]:
Recall that [tex]\( y = x^2 \)[/tex]. So we have:
[tex]\[ x^2 = 7 \][/tex]
and
[tex]\[ x^2 = -2 \][/tex]
Solving these equations for [tex]\( x \)[/tex]:
- For [tex]\( x^2 = 7 \)[/tex]:
[tex]\[ x = \pm \sqrt{7} \][/tex]
- For [tex]\( x^2 = -2 \)[/tex]:
[tex]\[ x = \pm \sqrt{-2} = \pm \sqrt{2}i \][/tex]
5. Combine all solutions:
The solutions to the equation [tex]\( x^4 - 5x^2 - 14 = 0 \)[/tex] are:
[tex]\[ x = \pm \sqrt{7} \quad \text{and} \quad x = \pm \sqrt{2}i \][/tex]
So, the correct answer is:
[tex]\[ x = \pm \sqrt{7} \quad \text{and} \quad x = \pm i \sqrt{2} \][/tex]
1. Substitute [tex]\( y = x^2 \)[/tex]:
This substitution simplifies the equation. Let [tex]\( y = x^2 \)[/tex], then the equation becomes:
[tex]\[ y^2 - 5y - 14 = 0 \][/tex]
2. Solve the quadratic equation [tex]\( y^2 - 5y - 14 = 0 \)[/tex]:
This is a standard quadratic equation. To solve it, we can use the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -5 \)[/tex], and [tex]\( c = -14 \)[/tex]. Plugging these values into the quadratic formula gives:
[tex]\[ y = \frac{5 \pm \sqrt{25 + 56}}{2} \][/tex]
[tex]\[ y = \frac{5 \pm \sqrt{81}}{2} \][/tex]
[tex]\[ y = \frac{5 \pm 9}{2} \][/tex]
3. Calculate the solutions for [tex]\( y \)[/tex]:
There are two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{5 + 9}{2} = \frac{14}{2} = 7 \][/tex]
and
[tex]\[ y = \frac{5 - 9}{2} = \frac{-4}{2} = -2 \][/tex]
4. Back-substitute [tex]\( y = x^2 \)[/tex] to find [tex]\( x \)[/tex]:
Recall that [tex]\( y = x^2 \)[/tex]. So we have:
[tex]\[ x^2 = 7 \][/tex]
and
[tex]\[ x^2 = -2 \][/tex]
Solving these equations for [tex]\( x \)[/tex]:
- For [tex]\( x^2 = 7 \)[/tex]:
[tex]\[ x = \pm \sqrt{7} \][/tex]
- For [tex]\( x^2 = -2 \)[/tex]:
[tex]\[ x = \pm \sqrt{-2} = \pm \sqrt{2}i \][/tex]
5. Combine all solutions:
The solutions to the equation [tex]\( x^4 - 5x^2 - 14 = 0 \)[/tex] are:
[tex]\[ x = \pm \sqrt{7} \quad \text{and} \quad x = \pm \sqrt{2}i \][/tex]
So, the correct answer is:
[tex]\[ x = \pm \sqrt{7} \quad \text{and} \quad x = \pm i \sqrt{2} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.